2017
DOI: 10.3168/jds.2017-12640
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of probiotic bacteria involved in fermented milk processing enriched with folic acid

Abstract: Yogurt products fermented with probiotic bacteria are a consumer trend and a challenge for functional food development. So far, limited research has focused on the behavior of the various probiotic strains used in milk fermentation. In the present study, we characterized folic acid production and the sensory and textural characteristics of yogurt products fermented with probiotic bacteria. Yogurt fermented with Lactobacillus plantarum had improved nutrient content and sensory and textural characteristics, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 21 publications
2
12
0
4
Order By: Relevance
“…In the food industry, the vitamins synthesized during the fermentation of lactic acid bacteria can be considered as nutritional fortification of food. This nutritional fortification expands the application of lactic acid bacteria to formulate fermented foods rich in certain vitamins for special populations ( Wu et al, 2017 ).…”
Section: Products Synthesized By Lactic Acid Bacteriamentioning
confidence: 99%
“…In the food industry, the vitamins synthesized during the fermentation of lactic acid bacteria can be considered as nutritional fortification of food. This nutritional fortification expands the application of lactic acid bacteria to formulate fermented foods rich in certain vitamins for special populations ( Wu et al, 2017 ).…”
Section: Products Synthesized By Lactic Acid Bacteriamentioning
confidence: 99%
“…Human milk contains mainly GSL called cerebrosides with nonhydroxylated fatty acid, whereas bovine milk contains mainly hydroxylated fatty acid (Newburg and Chaturvedi, 1992;Newburg, 1996;Chen et al, 2018). In addition, several studies have shown that goat milk and cow milk contain several GSL (Puente et al, 1994;Zancada et al, 2010) and vitamins (Wu et al, 2017).…”
mentioning
confidence: 99%
“…B. subtilis has been safely used as a probiotic and has been well tolerated in the clinical subjects without undesirable physiological effects (Lefevre et al., 2017). Different probiotics were used in milk revealing that L. plantarum was a good candidate for probiotic yogurt fermentation (Wu et al., 2017). It was suggested that the inclusion of microencapsulated bacteria by complex coacervation in yogurts could become an effective vehicle for successful delivery of probiotics to the gut, and hence contributing to the improvement of the gastrointestinal tract health, without altering the texture of the product (Bosnea et al., 2017).…”
Section: Discussionmentioning
confidence: 99%